Heightened metabolic responses in NK cells from patients with neuroblastoma suggests increased potential for immunotherapy - Slattery, Karen; Breheny, Megan; Woods, Elena; Keating, Sinead; Brennan, Kiva; Rooney, Caroline; Augustine, Sindhu; Ryan, Aishling; Owens, Cormac; Gardiner, Clair M. (Frontiers in Oncology, 2022)
High risk neuroblastoma is responsible for 15% of deaths in paediatric cancer patients. The introduction of anti-GD2 immunotherapy has significantly improved outcomes but there is still only approximately a 50% 5 year event-free-survival for these children and improvements in treatments are urgently required. Anti-GD2 immunotherapy uses the patients’ own immune system to kill cancer cells. In particular, Natural Killer (NK) cells kill antibody coated tumour cells by a process called antibody dependent cellular cytotoxicity (ADCC). However, our previous work has highlighted metabolic exhaustion of NK cells in circulating blood of adult cancer patients, identifying this as a potential therapeutic target. In this study, we investigated circulating NK cells in patients newly diagnosed with neuroblastoma. We found evidence of activation of NK cells in vivo by the cancer itself. While some evidence of NK cell dysfunction was observed in terms of IFN production, most results indicated that the NK cell compartment remained relatively intact. In fact, some aspects of metabolic and functional activities were actually increased in patients compared to controls. Glycolytic responses, which we show are crucial for ADCC, were actually enhanced in patients and CD16, the NK cell receptor that mediates ADCC, was also expressed at high levels in some patients. Overall, the data suggest that patient NK cells could be harvested at diagnosis for subsequent beneficial autologous use during immunotherapy. Enhancing glycolytic capacity of cell therapies could also be a strategic goal of future cell therapies for patients with neuroblastoma and indeed other cancers.